Shared patterns of species turnover between seaweeds and seed plants break down at increasing distances from the sea. Issue 1 (5th December 2013) - Gurgel, Carlos F. D.; Wernberg, Thomas; Thomsen, Mads S.; Russell, Bayden D.; Adam, Paul; Waters, Jonathan M.; Connell, Sean D.
Abstract We tested for correlations in the degree of spatial similarity between algal and terrestrial plants communities along 5500 km of temperate Australian coastline and whether the strength of correlation weakens with increasing distance from the coast. We identified strong correlations between macroalgal and terrestrial plant communities within the first 100 km from shore, where the strength of these marine–terrestrial correlations indeed weakens with increasing distance inland. As such, our results suggest that marine‐driven community homogenization processes decompose with increasing distance from the shore toward inland. We speculate that the proximity to the marine environment produces lower levels of community turnover on land, and this effect decreases progressively farther inland. Our analysis suggests underlying ecological and evolutionary processes that give rise to continental‐scale biogeographic influence from sea to land.